Rapid point-of-care HCV RNA quantification in capillary whole blood for diagnosing chronic HCV infection, monitoring treatment and detecting reinfection - Andrea Bregenzer; Nicole Warmann; Cornelia Ottiger; Christoph Andreas Fux (Swiss Medical Weekly, 2019)
BACKGROUND